Incorporating English Vocabulary Through the Use of Poster Media for Elementary School Students - Sri Wahyuningsih; Fifi Novita Fitriani (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2021)
The purpose of this study was to investigate how to incorporate English vocabulary among the third-grade students of MI NU Miftahul Huda 01 Karangmalang Gebog Kudus and its challenges. This study employed a qualitative research with a descriptive approach. Data were garnered through observation, interviews to the headmaster, teachers and students of MI NU Miftahul Huda 01 Karangmalang Gebog, and documentation. The results showed that the English vocabularies of students have significantly improved. It was evidenced by the enthusiastic response of students when participating in the learning process using poster media. In addition, through the use of poster media, students can easily memorize English vocabulary and its meanings on the poster media. Moreover, they are also able to pronounce English vocabulary. However, the obstacles of using poster media in teaching vocabulary include lack of motivation and confidence. This study offers an implication on the importance of using media in English language teaching particularly for young learners.